Added Value of Aortic Pulse Wave Velocity Index in a Predictive Diagnosis Decision Tree of Coronary Heart Disease. (9th January 2019) - Vallée, Alexandre; Petruescu, Laura; Kretz, Sandrine; Safar, Michel E; Blacher, Jacques
Abstract: BACKGROUND: Coronary heart disease (CHD) is among the main causes of death in the world. Individual study of cardiovascular risk is an important way to predict CHD risk. The aim of this study was to evaluate the added role of the aortic pulse wave velocity (PWV) index in the prediction of CHD risk. METHODS: A cross-sectional study was conducted from December 2012 to September 2017; 530 patients were included: 99 CHD, 338 non-CHD patients, and 93 nonhypertensives, nondiabetics and non-CHD subjects, whose theoretical PWV were calculated. Theoretical PWV was calculated according to age, blood pressure, gender, and heart rate. The results were expressed as an index ((measured PWV − theoretical PWV)/theoretical PWV) for each patient. The differences observed, the differential diagnostic performance, and the quantification of the added value of diagnostic performance of PWV index were tested using logistic regression, comparisons between receiver operating characteristic (ROC) curves, and decision tree nonlinear methodology. RESULTS: PWV index ( P = 0.006), carotid plaque ( P = 0.005), and dyslipidemia ( P = 0.04) were the independent modulators of CHD diagnosis. PWV index appears to be the highest specific classifier (81%) compared to carotid plaque (75%) and dyslipidemia (78%). For the decision tree, sensitivity, specificity, and area under the ROC curve for CHD diagnosis were 62%, 83%, and 0.87, respectively. CONCLUSIONS: PWV index yielded added value to CHD by assessment of combined classifiers with clinical determinants and decision tree construction and significantly increased the specificity of the differential diagnostic performances of the common risk factors of CHD in daily clinical practice.